Role of Relationship Marketing In Competitive Marketing Strategy: Exploring the Role of Relationship Marketing in Enhancing Business Performance (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Competitive Marketing Strategy (CMS) has relationshipmarketing (RM) as one of the key functionality in enhancing businessperformance. RM is defined as the identification, establishment, maintenance,enhancement, modification and termination of relationships with customers tocreate value for customers and profit for organization by a series of relationalexchanges that have both a history and a future. Relational exchanges can beviewed under transaction cost analysis and social exchange theories dependingon the context. The role of RM in CMS includes: guide moments of truth, improveprofitability, and build partnering, address ‘Customer Better’, buys in of customer attention, protectemotional wellbeing, understand consumer psyche, and build trust with customer.All these roles are observed empirically in the hotel industry, with somehotels placing emphasis on their extraordinary operations and services toengage with the customer.